Surgical management of gid disease in goat at Rangpur district of Bangladesh (Asian Journal of Medical and Biological Research, 2017)
The present study was conducted to know about the management of gid disease of goat at Upazila Veterinary Hospital, Rangpur Sadar and District Veterinary Hospital from July, 2011 to December, 2011 in Rangpur district at field level. A total of 12 goats were diagnosed based on history and presenting clinical sings. Furthermore, surgery was performed - in five cases. Circling movement, keeping the head downward to the affected side were major clinical sings. In all the cases, a half moon shaped incision was given at the operative site and after trephining the skull, the cyst was removed. The disease was predominant in female (91.66%) than male (16.66%). Among female goats, the prevalence of gid in pregnant and non-pregnant were 36.36% and 63.63% respectively. Black Bengal goats were more susceptible (91.66%) to this disease. The method of operation is considered to be useful as treatment in the field level. Alternative way of treatment using anthelmintics or other drugs have studied.Asian J. Med. Biol. Res. March 2017, 3(1): 109-113